Textiles in Ancient Mediterranean Iconography - Harris, Susanna (Oxbow Books, 2021)
This volume provides an ambitious synopsis of the complex, colourful world of textiles in ancient Mediterranean iconography. A wealth of information on ancient textiles is available from depictions such as sculpture, vase painting, figurines, reliefs and mosaics. Commonly represented in clothing, textiles are also present in furnishings and through the processes of textile production. The challenge for anyone analysing ancient iconography is determining how we interpret what we see. As preserved textiles rarely survive in comparable forms, we must consider the extent to which representations of textiles reflect reality, and critically evaluate the sources. Images are not simple replicas or photographs of reality. Instead, iconography draws on select elements from the surrounding world that were recognisable to the ancient audience, and reveal the perceptions, ideologies, and ideas of the society in which they were produced. Through examining the durable evidence, this anthology reveals the ephemeral world of textiles and their integral role in the daily life, cult and economy of the ancient Mediterranean.